The Influence of Spanish Pedagogy in Argentina during the Second Half of the Twentieth Century: the Case of Víctor García Hoz - Rodríguez, Laura Graciela (CIAN-Revista de Historia de las Universidades, 2016)
This article will analyze the interchanges that were established between the specialist in pedagogy, the Spanish named Víctor García Hoz (1911-1998) and Argentine education specialists among the decades from 1960 to 1980. This work is part of a long tradition of researches that analyze different aspects of the relations between Spanish people and Argentines at different times. More precisely, we want to inquire about the contents of their pedagogical proposals and how were read and appropriate in Argentine; how many times he visited Argentina and what type of activities he developed.
Keywords: pedagogy; Víctor García Hoz; España; Argentina; experimental sychology